Sinergitas Aktor Hubungan Masyarakat Dengan Media Dan Masyarakat Dalam Membangun Citra Institusi Perguruan Tinggi - Nurhanifah Nurhanifah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this study was to analyze the synergy of public relations actors with the media and society in building the image of higher education institutions. This type of research is qualitative research, data collection is done by observation and interviews. Finally, the data analysis obtained from the results of interview data processing was carried out. Then analyzed qualitatively. The stages of the analysis are to reduce data, present data, and finally draw conclusions. The findings of this study indicate that in enhancing the image of higher education institutions, public relations actors must synergize with the media and society by sharing information and data as a form of openness. The news about higher education institutions. The media has become an increasingly important stage for the external communication of institutions. Public relations has become a significant and powerful industry. Public relations actors work through the media to disseminate information, persuasion, and opinions to the public. So far, PR actors only build relationships with the media who work in areas that intersect with their work. Thus public relations in higher education are positioned as a liaison for the implementation of good cooperation between a university and the community.